Global Progress in Ecosystem-Based Fisheries Management 2012
DOI: 10.4027/gpebfm.2012.011
|View full text |Cite
|
Sign up to set email alerts
|

Do Species Interactions and Stochasticity Matter to Optimal Management of Multispecies Fisheries?

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…The diagonal elements are also relatively small, at least when compared to hypothetical scenarios studied in theoretical work (Poudel et al. []). The standard errors do not give a correct measure of the significance of the diagonal elements, as the elements are positive by definition, but nevertheless show that the system is stochastic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagonal elements are also relatively small, at least when compared to hypothetical scenarios studied in theoretical work (Poudel et al. []). The standard errors do not give a correct measure of the significance of the diagonal elements, as the elements are positive by definition, but nevertheless show that the system is stochastic.…”
Section: Resultsmentioning
confidence: 99%
“…We have in mind the type of analysis carried out in Sandal and Steinshamn [] and Poudel et al. []; see also Kugarajh et al. [].…”
Section: The Barents Sea Modelmentioning
confidence: 99%
“…The model captures much of the observed dynamics in the modelled populations, also in forecasting (an earlier study of the model that calculated two-year-ahead forecasts found that the main, dynamic features were picked up, but that forecasts tended to be low; see Ekerhovd and Kvamsdal, 2013). The low dimensionality is a key feature in that it makes economic analysis (that is,dynamic decision analysis; see Sandal and Steinshamn, 2010;Poudel et al, 2012) feasible, see Kvamsdal and Sandal (2014) for further discussion. Our e orts to model and estimate the Norwegian Sea pelagic complex combines a biological and ecological familiarity and understanding, the use of recent advances in data improvement (Ekerhovd and Gordon, 2013), and application of data assimilation methods (Evensen, 2003) that have seen little use in our eld.…”
Section: Resultsmentioning
confidence: 99%
“…We think there is a need for an explicit focus on modeling of biology and ecology that provides relevant structures for further, economic analysis (sensu Sandal and Steinshamn, 2010;Poudel et al, 2012). In our experience, biologists and ecologists have limited inherent interest in providing the necessary models, data, and structures.…”
mentioning
confidence: 99%
“…Therefore, it is a key approach for sustainable management (Hollowed et al, 2000) and consideration of multispecies interaction in fishery model is increasing in recent years (for example, see Agnarsson et al, 2008;Bogstad et al, 1997;Clark, 1990;Fleming & Alexander, 2003;Iversen, 2006;Kar & Chaudhuri, 2004;May et al, 1979;Poudel, Sandal, Steinshamn, & Kvamsdal, 2012;Sandal & Steinshamn, 2010;Woodward & Bishop, 1999;Yodzis, 1994). However, most of the studies focused on predators prey interactions between two species while three species continuous time interaction models are very few, although there is increasing interest in multispecies model in recent years (for example, Aanestad et al, 2009;Das, Srinivas, Srinivas, & Gazi, 2012;Nieminen, Lindroos, & Heikinheimo, 2012;Samanta, Manna, & Maiti, 2003;Sharma & Samanta, 2013).…”
Section: Introductionmentioning
confidence: 99%